Effects of Clavispora sp. co-fermented with Saccharomyces cerevisiae on physicochemical and aromatic profiles of blueberry wine - Ma, Yan; Guo, Zhi-qing; Cheng, Cheng; Chen, Jing; Wang, Zhi-Peng (Frontiers in Microbiology, 2026)
Blueberry wines provide a nutrient-rich alternative to perishable fresh fruits. However, the flavor complexity and nutrition retention remain limited by traditional fermentation. In this study, a non-Saccharomyces yeast Clavispora sp. LM32 was introduced into the Saccharomyces cerevisiae based blueberry fermentation. Ethanol levels were all reduced in simultaneous and sequential fermentation groups. Anthocyanin contents in simultaneous fermentation, sequential fermentation inoculating strain LM32 after 24 h (SEQ24), sequential fermentation inoculating strain LM32 after 48 h (SEQ48), were increased by 17.52, 38.59, and 43.87%, respectively. Meanwhile, SEQ24 brought significantly altered contents of volatile compounds, with higher alcohols increased by 19.85%, increased ethyl esters by 348.29%, acetate esters decreased by 18.43%, and synthesis of norisoprenoids and terpenes enhanced. Specially, contents of hexadecanoic acid ethyl ester and octanoic acid methyl ester in SEQ24 were increased by 4.6 times and 3.3 times, respectively, which can impart distinct tropical fruit and creamy fullness notes to the blueberry beverage. Sensory analysis demonstrated that sequential fermentation enhanced both fruity and sweet attributes. The study highlights the role of Clavispora sp. for enhancing aromatic profiles flavor and nutritional retention, proposing sequential fermentation as an optimal strategy for premium blueberry beverages.